Metode Dakwah Ustaz Obay kepada Anak Jalanan di Kecamatan Bojongloa Kaler Kota Bandung - Anita Syahrani; Nia Kurniati Syam; Malki Ahmad Nasir (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. The increasing number of street children in large cities like Bandung is a complex social problem. They live on the streets without adequate religious guidance, education, and affection, making them vulnerable to deviations such as drug abuse, violence, and other deviant behavior. In this context, da'wah plays a crucial role in fostering and guiding them towards a better life. This study aims to determine the da'wah method used by Ustaz Obay for street children and the challenges he faces. The title is